2008
DOI: 10.1007/s00520-008-0561-7
|View full text |Cite
|
Sign up to set email alerts
|

Infective and thrombotic complications of central venous catheters in patients with hematological malignancy: prospective evaluation of nontunneled devices

Abstract: Goals Central venous catheter (CVC)-related bloodstream infection (CR-BSI) is a significant complication in hematology patients. A range of CVC devices may be used, and risks for the development of complications are not uniform. The objectives of this study were to determine the natural history and rate of CVC-related complications and risk factors for CR-BSI and to compare device-specific complications in a hematology population. Patients and methods An observational cohort of patients with hematologic malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 23 publications
(20 reference statements)
7
69
1
2
Order By: Relevance
“…Our lower infection rate could be due to the fact that very few ICU patients were included in comparison with Gunst's and Chopra's cohorts [7,13]. However, this was partially offset by high recruitment of oncologic (64 %) and onco-hematologic (46 %) patients whom are known to be at increased risk of infection because of immunosuppression [14,15]. Yet, several authors reported that oncologic patients presented a higher PICC-related infection than non-oncologic ones: 6.61 per 1000 catheter-days in patients with hematological malignancies [15], 2.46 per 1000 catheter-days in oncologic patients (80 % of whom presented with solid tumors) [16] versus 1.1 per 1000 catheter-days in non-oncologic patients [4].…”
Section: Microbiologymentioning
confidence: 74%
See 3 more Smart Citations
“…Our lower infection rate could be due to the fact that very few ICU patients were included in comparison with Gunst's and Chopra's cohorts [7,13]. However, this was partially offset by high recruitment of oncologic (64 %) and onco-hematologic (46 %) patients whom are known to be at increased risk of infection because of immunosuppression [14,15]. Yet, several authors reported that oncologic patients presented a higher PICC-related infection than non-oncologic ones: 6.61 per 1000 catheter-days in patients with hematological malignancies [15], 2.46 per 1000 catheter-days in oncologic patients (80 % of whom presented with solid tumors) [16] versus 1.1 per 1000 catheter-days in non-oncologic patients [4].…”
Section: Microbiologymentioning
confidence: 74%
“…Yet, several authors reported that oncologic patients presented a higher PICC-related infection than non-oncologic ones: 6.61 per 1000 catheter-days in patients with hematological malignancies [15], 2.46 per 1000 catheter-days in oncologic patients (80 % of whom presented with solid tumors) [16] versus 1.1 per 1000 catheter-days in non-oncologic patients [4]. In our different sub-cohorts of solid neoplasia and hematologic malignancy patients, we also observed lower PICC-related infection rates than in the literature since ours are 1.45 and 3.13 per 1000 catheter-days respectively, versus 2.46 and 6.61 in oncologic and onco-hematologic patients, respectively [15,16]. Despite our low recruitment of ICU patients, we therefore considered that our PICC-related infection rate was low considering the proportion of oncologic patients in our study, especially the important inclusion of onco-hematologic ones, and the absence of outpatients whose PICC-related infection rate, according to the literature, is low (0.52 per 1000 catheter-days [17]).…”
Section: Microbiologymentioning
confidence: 96%
See 2 more Smart Citations
“…Esta duración es comparable con la literatura, que ha reportado duraciones de 72 días (31), 92 días (32), 113 días (33), entre otros. Además no se presentaron complicaciones asociadas al catéter como bacteriemias, tromboflebitis, taquicardias o trombosis, lo que contrasta con la complicaciones comunes reportadas por la literatura, especialmente en pacientes oncológicos (8,34,35,36,37); la ausencia de complicaciones pudo asociarse a la condición estable del paciente, el tipo de neoplasia y las condiciones óptimas para el cuidado intrahospitalario y domiciliario; esto último, apoya la evidencia de que enfermeras y cuidadores entrenados inciden en la disminución de complicaciones (38,39).…”
Section: Discussionunclassified